Belgian Anopheles plumbeus Mosquitoes Are Competent for Japanese Encephalitis Virus and Readily Feed on Pigs, Suggesting a High Vectorial Capacity - Claudia Van den Eynde; Charlotte Sohier; Severine Matthijs; Nick De Regge (Microorganisms, 2023)
Anopheles plumbeus, a day-active mosquito known to feed aggressively on humans, was reported as a nuisance species near an abandoned pigsty in Belgium. Since Japanese encephalitis virus (JEV) is an emerging zoonotic flavivirus which uses pigs as amplification hosts, we investigated (1) whether An. plumbeus would feed on pigs and (2) its vector competence for JEV, to investigate whether this species could be a potential vector. Three- to seven-day-old F0-generation adult mosquitoes, emerged from field-collected larvae, were fed on a JEV genotype 3 Nakayama strain spiked blood meal. Blood-fed mosquitoes were subsequently incubated for 14 days at two temperature conditions: a constant 25 °C and a 25/15 °C day/night temperature gradient. Our results show that An. plumbeus is a competent vector for JEV at the 25 °C condition and this with an infection rate of 34.1%, a dissemination rate of 67.7% and a transmission rate of 14.3%. The vector competence showed to be influenced by temperature, with a significantly lower dissemination rate (16.7%) and no transmission when implementing the temperature gradient. Moreover, we demonstrated that An. plumbeus readily feeds on pigs when the opportunity occurs. Therefore, our results suggest that Belgian An. plumbeus mosquitoes may play an important role in the transmission of JEV upon an introduction into our region if temperatures increase with climate change.